False Negative Toxoplasma Serology in an Immunocompromised Patient with PCR Positive Ocular Toxoplasmosis. (17th November 2018) - Rajput, Rehan; Denniston, Alastair K.; Murray, Philip I.
ABSTRACT: Purpose: The authors report a case of a 60-year-old Caucasian male with a background of treated Chronic Lymphocytic Leukaemia (CLL) with secondary hypogammaglobulinaemia present with toxoplasma chorioretinitis and negative serum toxoplasma serology on presentation and on subsequent reactivation. Methods: Retrospective case notes review with fundal photographs. Results: In this case, on initial presentation and on recurrence, the patient's serum anti-Toxoplasma IgG remained negative. The diagnosis was made on quantitative PCR of vitreous initially and aqueous humor on reactivation. Conclusions: Despite negative serology, one must still consider ocular toxoplasmosis especially in CLL patients where the clinical picture could be compatible. Hypogammaglobulinaemia, the inability to produce IgG antibodies, is a well-recognized complication of CLL. Intraocular fluid sampling is essential in these cases where the sensitivity of PCR on either aqueous or vitreous humor has been shown to be higher in immunocompromised patients.